Transgenic cucumber lines expressing the chimeric pGT:Dhn24 gene do not show enhanced chilling tolerance in phytotron conditions. Issue 4 (9th June 2015) - Mróz, Tomasz L.; Ziółkowska, Agnieszka; Gawroński, Piotr; Pióro‐Jabrucka, Ewelina; Kacprzak, Sylwia; Mazur, Magdalena; Malepszy, Stefan; Bartoszewski, Grzegorz; Debener, T.
Abstract In cucumber, low temperatures can result in chilling injuries and can lead to significant yield decreases in open field production. The lack of a cold‐tolerant cucumber germplasm has limited classical breeding. Recent progress in understanding plant response to cold stress has allowed to develop transgenic approaches to improving cold tolerance in chilling sensitive crop species. The pGT::Dhn24 gene construct containing an anthocyanidine glucosyltransferase promoter and the DHN24 dehydrin‐encoding gene originating from cold‐acclimated species Solanum sogarandinum was developed, and preliminary study showed that its expression could increase cucumber chilling tolerance. In this study, a set of transgenic cucumber lines was developed and tested for cold tolerance. Expression of pGT::Dhn24 was confirmed in the transgenic cucumber lines at both the transcript and protein level. At the protein level, chilling‐induced pGT::Dhn24 transgene expression was observed in the leaves; however, it was constitutive in the roots. Cold stress‐related physiological parameters, germination ability and severity of chilling injury were measured for the transgenic lines at the phytotron conditions. No evidence for increased cold tolerance of the transgenic cucumber lines was found.